TRANSFORMAREA BIBLIOTECARILOR ÎN PROFESIONIȘTI AI INOVAȚIEI - KULIKOVSKI, Lidia (BIBLIOPOLIS, 2020)
Every librarian can become an innovative professional with the condition that he has an appropriate educational support and tools. The improving of the innovation management quality depends of the quality of innovative thinking. To realize this we should explore the perception’s custom of the innovators. The successful innovators compromise the obsolete conventionality; pay attention to the emerging trends; use the human competencies; can identify the needs of users. If the librarians will develop the skills and competencies in order to pass from the obsolete conventionality and understand the emerging trends, if they can see the users needs, they could become innovators in their field.